Manajemen Strategik dalam Menangkal Radikalisme di Perguruan Tinggi Islam - Khairul Saleh; Noor Malihah; Umar Fauzan; Muhammad Arbain (FENOMENA, 2021)
This study aims to formulate the concept of strategic management in overcoming radicalism through deradicalization based on Islamic education. Direct observations were made to map the strategic management used by each Islamic university in the deradicalization process. In addition, Focus Group Discussions were also held during the data collection process in order to dig deeper into the policies of the managers and to confirm what researchers found on direct observation of lecturers related to the implementation of deradicalization. In addition, to support these results, semi-structured interviews were conducted with student representatives from each Islamic university to highlight their perspectives on realizing deradicalization through Islamic education. The results showed that, (1). Deradicalization in Islamic universities can be done by formulating an inclusive-multicultural Islamic education curriculum; (2) training educators (teachers) with an inclusive-multicultural paradigm who are full of creativity in the management of unique and interesting learning with different emphases and high tolerance, multicultural and humanistic values and become ambassadors of anti-radicalism education in the social field to lead the media; (3) evaluate the deradicalization of inclusive multicultural Islamic education directed at the right goals.